Serum IgG2 antibody multicomposition in systemic lupus erythematosus and lupus nephritis (Part 1): cross-sectional analysis. (29th December 2020) - Bruschi, Maurizio; Moroni, Gabriella; Sinico, Renato Alberto; Franceschini, Franco; Fredi, Micaela; Vaglio, Augusto; Cavagna, Lorenzo; Petretto, Andrea; Pratesi, Federico; Migliorini, Paola; Locatelli, Francesco; Pazzola, Giulia; et al.
Abstract: Objectives: Serum anti-dsDNA and anti-nucleosome IgGs have been proposed as signatures for SLE and LN in limited numbers of patients. We sought to show higher sensitivity and specificity of the same antibodies with the IgG2 isotype and included IgG2 antibodies vs specific intracellular antigens in the analysis. Methods: A total of 1052 SLE patients with ( n = 479) and without ( n = 573) LN, recruited at different times from the beginning of symptoms, were included in the study. Patients with primary APS (PAPS, n = 24), RA (RA, n = 24) and UCTD (UCTD, n = 96) were analysed for comparison. Anti-nucleosome (dsDNA, Histone2A, Histone3), anti-intracellular antigens (ENO1), anti-annexin A1 and anti-C1q IgG2 were determined by non‐commercial techniques. Results: The presence in the serum of the IgG2 panel was highly discriminatory for SLE/LN vs healthy subjects. Serum levels of anti-dsDNA and anti-C1q IgG2 were more sensitive than those of IgGs (Farr radioimmunoassay/commercial assays) in identifying SLE patients at low–medium increments. Of more importance, serum positivity for anti-ENO1 and anti-H2A IgG2 discriminated between LN and SLE (ROC T0–12 months ), and high levels at T0–1 month were detected in 63% and 67%, respectively, of LN, vs 3% and 3%, respectively, of SLE patients; serum positivity for each of these was correlated with high SLEDAI values. Minor differences existed between LN/SLE and the other rheumatologic conditions. Conclusion: Nephritogenic IgG2 antibodies represent a specific signature of SLE/LN, with a few overlaps with other rheumatologic conditions. High levels of anti-ENO1 and anti-H2A IgG2 correlated with SLE activity indexes and were discriminatory between SLE patients limited to the renal complication and other SLE patients. Trial registration: The Zeus study was registered at https://clinicaltrials.gov, NCT02403115.